Problem Analysis of Science Learning Based on Local Wisdom: Causes and Solutions - Hikmawati Hikmawati; Ketut Suma; I Wayan Subagia (Postgraduate, University of Mataram, 2021)
This study aims to analyze the problematic analysis of science learning based on local wisdom and the solution in terms of its solution in terms of several aspects, namely: curriculum, teachers, students, learning strategies, assessments, facilities and infrastructure. This type of research is descriptive qualitative. The research data was obtained through literature review and giving questionnaires to 65 respondents. The respondents came from 201 teachers who are alumni at one of the universities in Mataram City who are members of WAG IKA (WhatsApp Group Alumni Association). The questionnaire contains a list of six open-ended questions. The results of the study provide information that curriculum changes are expected to answer the needs of the times and consider local wisdom according to the characteristics of each region, these changes require mental changes from curriculum implementers. The quantity of teachers is sufficient but the quality of teachers still needs to be improved, especially in designing learning tools based on local wisdom. From the student factor, the role of parents as well as motivation and interest in learning is important to improve so that learning outcomes are as expected, and students also care about local wisdom in their neighborhood. For this reason, teachers need good learning strategies in planning local wisdom-based learning processes in the classroom by considering authentic assessments that are able to measure aspects of students' attitudes, knowledge, and skills in learning science. Facilities and infrastructure that can support science learning activities based on local wisdom include: library facilities, science laboratories, multimedia laboratories, and objects of local wisdom around students.